Using developmental bibliotherapy design to improve self-management skills of post-graduate students. Issue 2 (3rd April 2023) - Sharma, Daneshwar
ABSTRACT: Students come to schools and college to not only learn academic subjects but also gain personal effectiveness skills for life. During the developmental and transition phase of growing up, young students can face a lot of issues and problems related to the self and their surroundings. The participants of this research were post-graduate management students who suffered from a lack of self-management skills. A reading course/intervention based on Shrodes (1950) model of bibliotherapy was developed. Using developmental and didactic bibliotherapy based on CBT a short reading course was conducted with 138 students. Reflective writing and discussion activities were conducted along with group reading. The impact of the reading course/intervention was analyzed using descriptive research methods (paired sample t -test) and qualitative reading of the reflective writing. The intervention has been successful in bringing positive habit formation and attitude change in the students.